2014
DOI: 10.1530/joe-13-0502
|View full text |Cite
|
Sign up to set email alerts
|

Administration of 3,5‐diiodothyronine (3,5‐T2) causes central hypothyroidism and stimulates thyroid‐sensitive tissues

Abstract: In general, 3,5-diiodothyronine (3,5-T2) increases the resting metabolic rate and oxygen consumption, exerting short-term beneficial metabolic effects on rats subjected to a high-fat diet. Our aim was to evaluate the effects of chronic 3,5-T2 administration on the hypothalamus–pituitary–thyroid axis, body mass gain, adipose tissue mass, and body oxygen consumption in Wistar rats from 3 to 6 months of age. The rats were treated daily with 3,5-T2 (25, 50, or 75 μg/100 g body weight, s.c.) for 90 days between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 49 publications
12
62
0
Order By: Relevance
“…But in contrast to these beneficial effects, an undesired negative feedback inhibition of the hypothalamuspituitary-thyroid (HPT) axis accompanied by increased heart weight was observed at the dose effectively improving hepatic lipid metabolism and systemic lipid status (Jonas et al 2014). Such observations on doserelated thyromimetic actions, among others also on the pituitary and the heart, are in agreement with published results on mice and rats treated with 3,5-T 2 (Horst et al 1995, Goldberg et al 2012, Padron et al 2014.…”
Section: Introductionsupporting
confidence: 86%
“…But in contrast to these beneficial effects, an undesired negative feedback inhibition of the hypothalamuspituitary-thyroid (HPT) axis accompanied by increased heart weight was observed at the dose effectively improving hepatic lipid metabolism and systemic lipid status (Jonas et al 2014). Such observations on doserelated thyromimetic actions, among others also on the pituitary and the heart, are in agreement with published results on mice and rats treated with 3,5-T 2 (Horst et al 1995, Goldberg et al 2012, Padron et al 2014.…”
Section: Introductionsupporting
confidence: 86%
“…Our investigations were aimed at assessing the suppressive effects of this molecule on the pituitary-thyroid axis. 7 In line with the recent findings of Padron and colleagues, 6 our data show that the administration of 3,5-diiodo-L-thyronine to rats three times a week up to 4 weeks leads to a reduction in BW gain despite the decreased level of T4 and T3 serum levels. On the other hand, Lanni and colleagues 8 have shown that the administration of 25 mg/100 g of 3,5-T2 to rats may reduce BW gain and adiposity while no change in serum T4 levels was observed in animals fed a diet rich in fat and treat- ed with 3,5-T2.…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in thyroid hormone levels may be secondary to the reduction in serum levels of TSH, which leads to a reduced activity and expression of sodium-iodide symporter (NIS), thyroid D1, and thyroid peroxidase (TPO). 6 These new data support the hypothesis that 3,5-T2 causes exogenous TSH suppression. Thus, 3,5-T2 may be used as a non-thyreomimetic pharmacological agent in the treatment of hypothyroidism.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Also, stimulation of the cytochrome oxygenase was noted, but this data has not yet been independently confirmed. While only a few possible biological effects of 3,3′-T 2 and 3′,5′-T 2 have been reported, there is more information available for 3,5-T 2 , which circulates in human serum [26] and might rapidly and directly act on mitochondrial function and at higher concentrations also mimics T 3 effects via modulation of TR-dependent transcription in many target cells [27,28,29,30,31]. Moreover, it was recently demonstrated that 3,5-T 2 influences the volume of adipocytes by inducing lipolysis and increases the mitochondrial content in brown adipocytes and thermogenesis, thus demonstrating an influence of 3,5-T 2 on the metabolism [32].…”
Section: Discussionmentioning
confidence: 99%